201k views
4 votes
(3x+15) (6x+3) m<1 is

(3x+15) (6x+3) m<1 is-example-1

1 Answer

5 votes

Answer:

x = 4

Explanation:

Simplifying

3x + 15 = 6x + 3

Reorder the terms:

15 + 3x = 6x + 3

Reorder the terms:

15 + 3x = 3 + 6x

Solving

15 + 3x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.

15 + 3x + -6x = 3 + 6x + -6x

Combine like terms: 3x + -6x = -3x

15 + -3x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0

15 + -3x = 3 + 0

15 + -3x = 3

Add '-15' to each side of the equation.

15 + -15 + -3x = 3 + -15

Combine like terms: 15 + -15 = 0

0 + -3x = 3 + -15

-3x = 3 + -15

Combine like terms: 3 + -15 = -12

-3x = -12

Divide each side by '-3'.

x = 4

Simplifying

x = 4

User Bennylope
by
6.0k points